Cutaneous disorders in 500 diabetic patients attending diabetic clinic - Shivanna Ragunatha; Bhaktavatsalam Anitha; Arun C Inamadar; Aparna Palit; Shashidhar S Devarmani (Wolters Kluwer Medknow Publications, 2011)
Background: The metabolic complications and pathologic changes that occur in diabetes mellitus (DM) influence the occurrence of various dermatoses. Aim: To study the impact of control of diabetes on the pattern of cutaneous disorders. Materials and Methods: A cross-sectional descriptive study of patients attending diabetic clinic in a tertiary care hospital. A total of 500 consecutive patients were studied. Detailed history, clinical examination and relevant investigations were done to diagnose diabetic complications and cutaneous disorders. Dermatoses with or without known pathogenesis were correlated with age, gender, fasting plasma glucose (FPG), duration of diabetes, and complications of DM. Statistical analysis was carried out using Student "t" test and Chi-square test with 5% confidence interval (P value 0.05). Results: Majority of patients had well-controlled (FPG<130 mg/ml, 60%) type 2 DM (98.8%). No statistically significant difference (P>0.05) between the patients with or without DM specific cutaneous disorders was noticed with reference to age and gender distribution, duration of DM and FPG. Signs of insulin resistance, acrochordon (26.2%), and acanthosis nigricans (5%) were common, followed by fungal (13.8%) and bacterial (6.8%) infections. Eruptive xanthoma (0.6%), diabetic foot (0.2%), diabetic bulla (0.4%), diabetic dermopathy (0.2%), generalized granuloma annulare (0.2%), and insulin reactions (6.2%) and lipodystrophy (14%) were also seen. Conclusion: Well-controlled diabetes decreases the prevalence of DM-specific cutaneous disorders associated with chronic hyperglycemia. It is necessary to have a dermatologist in the diabetic clinic for early detection of potentially grave or predisposing conditions.